FREQUENCY ANALYSIS OF DELTA SCUTI VARIABLE STARS. I. - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
The Fourier analyses are performed for photoelectric observations of two δ Scuti stars V567 Oph and KU Cen. It is shown that V567 Oph is a multiperiodic star and KU Cen has one main period.